PENGARUH PENGGUNAAN MEDIA WORDWALL TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK USIA DINI DI TAMAN KANAK-KANAK HARAPAN KITA PAINAN - Dwiva Insya Hila Hiya; Rakimahwati; Yulsyofriend; Zulminiati (STKIP Subang, 2026)
This research is motivated by the low early reading skills of young children at Harapan Kita Painan Kindergarten. This low level of ability is caused by the lack of variety in learning media used by teachers, resulting in children being less interested and less active in participating in reading learning activities. One alternative learning medium that can be used is Wordwall, a digital-based, interactive learning medium that can increase children's engagement in the learning process. This study aims to determine the effect of using Wordwall on the early reading skills of young children at Harapan Kita Painan Kindergarten. This study used a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The subjects were 22 children in Group B at Harapan Kita Painan Kindergarten, consisting of 11 children in the experimental class and 11 children in the control class. Data collection used a six-item early reading skills test. Data analysis techniques included normality tests, homogeneity tests, and hypothesis testing using the independent sample t-test (SPSS version 27). Based on the results of the post-test hypothesis test, the Sig. (2-tailed) value was 0.067. These results indicate a difference in average early reading ability between the experimental and control classes. The average post-test score for the experimental class was 20.45, higher than the average post-test score for the control class of 19.36. Therefore, it can be concluded that the use of Wordwall media has a positive impact on the early reading ability of early childhood children at Harapan Kita Kindergarten, Painan.